Static and seismic analysis of an arch-gravity dam - Mitovski S., Kokalanov G., Petkovski L., Tancev L. and Veleski G. (Royal Institute of Technology (KTH) Department of Civil and Architectural Engineering Division of Concrete Structures Stockholm, Sweden, 2018, 2017)
The Janneh dam is designed as an arch-gravity RCC dam (H=157 m), and currently is under construction. It was initially designed as a straight-gravity dam. However, due to seismic reasons, its layout has been curved. The 2D section of the central block does not satisfy the generally adopted stability criteria for straight gravity dams. The stability of the dam relies consequently on its 3D behavior. In the paper is performed numerical analysis of dam Janneh, thus applying total of 8 models. Namely, the dam was analyzed on action of static and seismic loads (spectral analysis and time history analysis). For research of the behaviour of the contact zone dam-foundation were applied interface elements.